2021
DOI: 10.1016/j.heliyon.2021.e07151
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii: A possible etiologic agent for Alzheimer's disease

Abstract: Toxoplasma gondii ( T. gondii ) is one of the most pervasive neurotropic pathogens causing different lesions in a wide variety of mammals as intermediate hosts, including humans. It is estimated that one-third of the world population is infected with T. gondii ; however, for a long time, there has been much interest in the examination of the possible role of this parasite in the development of mental disorders, such as Alzheimer's disease (AD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 234 publications
(290 reference statements)
0
10
0
Order By: Relevance
“…It has been described that it can induce immune response in the host and inflammation in the CNS, alteration in the levels of neurotransmitters, and direct infections of neuronal and astrocytic cells (in rat primary cell culture) ( Luder et al, 1999 ). For these reasons, T. gondii can be considered a possible etiologic risk factor for Alzheimer’s disease ( Nayeri et al, 2021 ).…”
Section: Gut Brain and Brain Pathologiesmentioning
confidence: 99%
“…It has been described that it can induce immune response in the host and inflammation in the CNS, alteration in the levels of neurotransmitters, and direct infections of neuronal and astrocytic cells (in rat primary cell culture) ( Luder et al, 1999 ). For these reasons, T. gondii can be considered a possible etiologic risk factor for Alzheimer’s disease ( Nayeri et al, 2021 ).…”
Section: Gut Brain and Brain Pathologiesmentioning
confidence: 99%
“…In addition, Toxoplasma infection can increase neural cell death, alteration in neural gene expression and the release of inflammatory mediators in neurospheres [ 132 ]. Thus, this infection could be correlated with psychiatric diseases and human CNS disorders including Alzheimer, dementia, depression and schizophrenia [ 54 , 133 , 134 , 135 , 136 ]. On the other hand, due to the overexpression of complement components in Toxoplasma -infected brain [ 53 , 63 ], and the upregulation of C1q, C3, and C4b in some mental disorders including schizophrenia, alzheimer’s disease, aging and multiple sclerosis [ 54 , 137 , 138 , 139 , 140 ], it could be interesting to focus on therapeutic studies that share more information regarding the possible correlations between parasitic disease including toxoplasmosis and mental disorders and their association with the complement system.…”
Section: Potential Targets Based On Protozoa-host’s Complement Intera...mentioning
confidence: 99%
“…Chronic T. gondii infection affects almost one-third of the global population [4,5]. Numerous epidemiological statistics suggested that the positive rate of serum Toxoplasma antibodies in AD patients was higher than that in the control group [6]. Toxoplasma gondii can enter the brain from various anatomical sites to form tissue cysts through the blood-brain barrier and erode neurons, astrocytes and microglia [7][8][9].…”
Section: Introductionmentioning
confidence: 99%